Does Corporate Social Responsibility Heterogeneity Affect Corporate Financial Performance Through Technological Innovation? The Moderating Effects of Advertising Intensity - Niu, Mengxi; Ma, Wentao (Frontiers in Psychology, 2022)
In this study, we examine the effects of firms’ corporate social responsibility (CSR), technological innovation, and advertising intensity on corporate financial performance (CFP). Prior research has shown mixed findings for the CSR–CFP relationship. To provide additional evidence and alternative explanations for these mixed findings, we build a moderated mediating model by combining the knowledge-based view with the stakeholder theory. We use this model to examine whether CSR influences CFP through affecting technological innovation and whether such mediating effects are moderated by advertising intensity. We classify heterogeneous CSR activities into technical and institutional activities. Using data from 2010 to 2018 on Chinese listed firms, we find that superior technical CSR performance can enhance CFP by promoting technological innovation and that it promotes technological innovation to a greater extent when advertising intensity is higher. However, although institutional CSR is also positively related to technological innovation, it does not affect CFP. The findings suggest that to improve the firm’s financial position, its resources should be allocated effectively to technical CSR activities as well as to innovation and advertising.